Congenital microtia and congenital aural atresia: A literature review: Microtia y atresia aural congénita: una revisión de la literatura - Marin Marin, Diego (2024)
Permanent hearing loss is common at birth, and the negative consequences for language, cognitive, and social-emotional skills are particularly important. Microtia and congenital aural atresia is a disorder of the external ear that can occur in isolation or in association with another malformation. The objective of the present study was to know and compile the current evidence on microtia and aural atresia. The PubMed, Scopus, and SciELO databases were consulted, from the year 2010 to the year 2023. All the bibliographic references were searched in relation to the keywords: microtia, and aural atresia. Were evaluated review and research articles, which in general, were less than 05 years published. It was limited to articles in Spanish and English and were identified by titles. Were identified once the articles of interest, the following were considered as inclusion criteria: 1. That they examine the diagnosis and treatment of microtia and congenital aural atresia 2. They address the subject according to a systematic methodology (quantitative, qualitative, and others). The causes of these disorders are not fully understood. In conclusion, auditory evoked potentials and audiometry are the test of choice for cases of microtia and congenital aural atresia. Surgical correction is often not the preferred treatment; the hearing result is no better than that of bone conduction devices. Likewise, the functional aspect should be prioritized over the aesthetic one since early hearing loss intervenes in the development of language in the child.